Evidence for G‐Protein–Coupled Estrogen Receptor as a Pronatriuretic Factor - Gohar, Eman Y. (J Am Heart Assoc, 2020)
BACKGROUND: The novel estrogen receptor, G‐protein–coupled estrogen receptor (GPER), is responsible for rapid estrogen signaling. GPER activation elicits cardiovascular and nephroprotective effects against salt‐induced complications, yet there is no direct evidence for GPER control of renal Na(+) handling. We hypothesized that GPER activation in the renal medulla facilitates Na(+) excretion. METHODS AND RESULTS: Herein, we show that infusion of the GPER agonist, G1, to the renal medulla increased Na(+) excretion in female Sprague Dawley rats, but not male rats. We found that GPER mRNA expression and protein abundance were markedly higher in outer medullary tissues from females relative to males. Blockade of GPER in the renal medulla attenuated Na(+) excretion in females. Given that medullary endothelin 1 is a well‐established natriuretic factor that is regulated by sex and sex steroids, we hypothesized that GPER activation promotes natriuresis via an endothelin 1–dependent pathway. To test this mechanism, we determined the effect of medullary infusion of G1 after blockade of endothelin receptors. Dual endothelin receptor subtype A and endothelin receptor subtype B antagonism attenuated G1‐induced natriuresis in females. Unlike males, female mice with genetic deletion of GPER had reduced endothelin 1, endothelin receptor subtype A, and endothelin receptor subtype B mRNA expression compared with wild‐type controls. More important, we found that systemic GPER activation ameliorates the increase in mean arterial pressure induced by ovariectomy. CONCLUSIONS: Our data uncover a novel role for renal medullary GPER in promoting Na(+) excretion via an endothelin 1–dependent pathway in female rats, but not in males. These results highlight GPER as a potential therapeutic target for salt‐sensitive hypertension in postmenopausal women.